Student Perception and Comparison of their Academic Performance in Online Formative Assessment Vs Summative Assessment during Covid Period - Uzma Naseer, Tayyaba Mahmud (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Covid pandemic forced the teachers and students to adopt e-learning to replace traditional pedagogy. Aim: To see student perception on altered teaching methodology, its effectiveness by comparison of their academic performance. Methodology: In this cross-sectional analytical study, 141 students of 1st year MBBS (session 2019-20), participated. After taking informed consent, data was collected from score sheets of online formative assessment, ‘Socrative,’ and marks obtained in on-campus summative assessment in histology. Different parameters regarding student perception for e-learning and assessment were measured by using a 5-point Likert-scale questionnaire. Data were analyzed using SPSS version 26. Results: Paired Samples t-test was used to see the effectiveness of online teaching and was found to be insignificant (P = 0.307). Pearson Chi-square test showed a statistically significant result (P < 0.001) between the responses on learning and assessment tools, with linear association, (P value < 0.001). A correlation between learning and assessment scores (r= 0.727, P value < 0.001) was observed. Conclusion: Online learning can assist the teaching process in medical studies without influencing their academic performance. Practice of online teaching has prepared both students and teachers for blended learning in routine days as well as in case of a future pandemic. MeSH Keywords: Feedback, Academic Performance, Perception